KEMAMPUAN PEMECAHAN MASALAH FISIKA PADA MATERI USAHA DAN DAYA BERDASARKAN LANGKAH-LANGKAH HELLER - Indrawati, Anis; Darmadi, I Wayan (Universitas Tadulako, 2021)
This study aimed to obtain a description of physics problem solving on work and power of 8 graders of SMP Labschool UNTAD Palu based on Heller's steps in terms of the students who have high, medium and low ability categories. This research was qualitative research. Respondents involved in this study consisted of 6 students, each 2 were from high, medium and low ability categories. The data were obtained through a problem-solving ability test consisting of 5 questions and interviews. The results of this study indicate that respondents in the high and medium categories have very good abilities in solving the given Physics problems, especially in terms of identifying and writing down things that are known and asked, making connections between existing information and the problems being asked, and implementing solving strategies. problem based on the concept of work and power. Meanwhile, respondents in the low category have very little ability to solve problems because students do not have a single problem-solving solution plan based on Heller's steps.